Literature Review : Implementasi Algoritma K-Means Clustering Dalam Berbagai Sektor - Janter Tampubolon, Rivaldo; Ariesandes, Thoty; Idlal Hafizd, Muhammad; Hidayatullah, Najwan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
K-Means Clustering is a crucial machine learning algorithm that plays a significant role in modern data analysis and information processing. This research aims to examine the application of K-Means Clustering through a systematic review of scientific journals. The literature study explores the implementation of K-Means in four different fields: public health, education, marketing, and agriculture. The research methodology employed a comparative analysis of published journals, focusing on methodologies, results, and practical implications of clustering algorithm usage. The findings demonstrate that K-Means possesses high flexibility in identifying patterns and supporting cross-domain decision-making processes.